2017
DOI: 10.1123/tsp.2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of REBT, and the Use of Credos, on Irrational Beliefs and Resilience Qualities in Athletes

Abstract: The use of rational emotive behavior therapy (REBT) in sport psychology has received little attention in research to date, but is steadily growing. Therefore, to further add to the building body of research, this study examines the efficacy of REBT (comprising five counseling sessions, and four homework assignments) in decreasing self-reported irrational beliefs, and increasing self-reported resilient qualities in five elite squash players from Malaysia. The study uses a single-case multiple-baseline across-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 22 publications
1
29
0
2
Order By: Relevance
“…The iPBI has demonstrated construct and concurrent validity in organisational settings with strong fit indices (CFI = 0.93, NNFI = 0.92, SRMR = 0.06, RMSEA = 0.07) and positive correlations between similar subscales of a corresponding measure of irrational beliefs -the shortened general attitude and belief scale (Lindner, Kirkby, Wertheim, & Birch, 1999). The questionnaire was developed for achievement contexts in general and has been used to measure irrational beliefs in athletic samples (Deen et al, 2017;Turner et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The iPBI has demonstrated construct and concurrent validity in organisational settings with strong fit indices (CFI = 0.93, NNFI = 0.92, SRMR = 0.06, RMSEA = 0.07) and positive correlations between similar subscales of a corresponding measure of irrational beliefs -the shortened general attitude and belief scale (Lindner, Kirkby, Wertheim, & Birch, 1999). The questionnaire was developed for achievement contexts in general and has been used to measure irrational beliefs in athletic samples (Deen et al, 2017;Turner et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…This involves recognising that irrational beliefs cause emotional and behavioural consequences (rather than the event itself) and then encouraging dispute of the irrational thought and promoting and reinforcing rational thoughts. In sport settings, irrational beliefs have been identified as important for the experience of anxiety (Turner & Barker, 2013), self-acceptance (Cunningham & Turner, 2016), burnout (Turner & Moore, 2016), resilience (Deen, Turner, & Wong, 2017), psychological distress (Turner, Carrington, & Miller, 2017), and task performance (Wood, Turner, Barker, & Higgins, 2017). Research in nonsport settings also reveals that irrational beliefs are associated with an array of emotional and behavioural malfunctioning (Visla, Fluckiger, Holtforth, & David, 2016) that could also afflict athletes (Turner, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of research examining the use of REBT in performance settings has been conducted using Western, mainly European, participant samples. There are two exceptions that have applied REBT with athletes in a Malaysian (Deen, Turner, & Wong, 2017) and a Chinese (Si & Lee, 2008) sample. Deen et al (2017) found that REBT was able to reduce irrational beliefs and increase self-reported resilience in Malaysian squash players, and Si and Lee (2008) found a reduction in behaviors related to LFT, and performance enhancement in competition, in an Olympic table tennis athlete.…”
mentioning
confidence: 99%
“…There are two exceptions that have applied REBT with athletes in a Malaysian (Deen, Turner, & Wong, 2017) and a Chinese (Si & Lee, 2008) sample. Deen et al (2017) found that REBT was able to reduce irrational beliefs and increase self-reported resilience in Malaysian squash players, and Si and Lee (2008) found a reduction in behaviors related to LFT, and performance enhancement in competition, in an Olympic table tennis athlete. However, whether and to what extent REBT can be applied in Eastern samples is not fully understood, and research findings using Western samples cannot be automatically generalised to Eastern samples.…”
mentioning
confidence: 99%